Factors Influencing the Immediate Graduate Study Enrollment of English Language Teachers - Legion, Rheaflor; Baldicañas, Hazel Joy (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigates the factors influencing immediate graduate study enrollment among English Language Teachers (ELTs) at Eastern Samar State University, Borongan Campus. Anchored on Self-Determination Theory, Expectancy-Value Theory, and Human Capital Theory, the research employs a descriptive–correlational design to examine the roles of intrinsic motivation, extrinsic motivation, financial capability, and program accessibility in shaping ELTs’ decisions to pursue postgraduate studies within three years of completing their undergraduate degrees. A structured survey questionnaire was administered to 44 respondents selected via convenience sampling. Results indicate that intrinsic motivation significantly drives personal growth, intellectual fulfillment, and professional mastery, while extrinsic motivation, particularly career advancement, salary increase, and qualification requirements, strongly influences enrollment decisions. Financial capability, including tuition affordability and availability of resources, affects access to graduate programs, whereas program accessibility, encompassing quality of faculty, program specialization, flexible schedules, and online learning options, was identified as a very high influencing factor. Demographic analysis shows significant associations between timing of enrollment and age, year of bachelor’s graduation, and employment status, highlighting that younger and recently graduated teachers are more likely to enroll immediately. The study concludes that immediate graduate study enrollment is shaped by a combination of personal, financial, and institutional factors, and recommends enhancing program accessibility, financial support mechanisms, and institutional policies to facilitate timely graduate education. Findings are particularly relevant for policy-making, institutional planning, and career guidance for early-career ELTs. The study aligns with SDG 4 (Quality Education) and SDG 8 (Decent Work and Economic Growth), supporting sustainable teacher professional development and career advancement. Its sustainability impact includes fostering educational and socio-economic sustainability through enhanced access, professional competency, and institutional support for early-career educators.
Keywords: Career Advancement; English Language Teachers; Extrinsic Motivation; Financial Capability; Graduate Program Accessibility; Immediate Enrollment; Intrinsic Motivation; Professional Development; Self-Determination